Odpowiedź:
1 - 1/7 = 7/7 - 1/7 = 6/7
2 - 1/7 = 1 i 7/7 - 1/7 = 1 i 6/7
6 - 1/7 = 5 i 7/7 - 1/7 = 5 i 6/7
10 - 1/7 = 9 i 7/7 - 1/7 = 9 i 6/7
1 - 5/6 = 6/6 - 5/6 = 1/6
2 - 5/6 = 1 i 6/6 - 5/6 = 1 i 1/6
5 - 5/6 = 4 i 6/6 - 5/6 = 4 i 1/6
7 - 5/6 = 6 i 6/6 - 5/6 = 6 i 1/6
2 - 1 i 3/11 = 1 i 11/11 - 1 i 3/11 = 8/11
3 - 1 i 3/11 = 2 i 11/11 - 1 i 3/11 = 1 i 8/11
5 - 1 i 3/11 = 4 i 11/11 - 1 i 3/11 = 3 i 8/11
8 - 1 i 3/11 = 7 i 11/11 - 1 i 3/11 = 6 i 8/11
3 - 2 i 5/9 = 2 i 9/9 - 2 i 5/9 = 4/9
5 - 2 i 5/9 = 4 i 9/9 - 2 i 5/9 = 2 i 4/9
12 - 2 i 5/9 = 11 i 9/9 - 2 i 5/9 = 9 i 4/9
20 - 2 i 5/9 = 19 i 9/9 - 2 i 5/9 = 17 i 4/9